2016
DOI: 10.1016/j.jtbi.2015.11.008
|View full text |Cite
|
Sign up to set email alerts
|

The overshoot and phenotypic equilibrium in characterizing cancer dynamics of reversible phenotypic plasticity

Abstract: The paradigm of phenotypic plasticity indicates reversible relations of different cancer cell phenotypes, which extends the cellular hierarchy proposed by the classical cancer stem cell (CSC) theory. Since it is still questionable if the phenotypic plasticity is a crucial improvement to the hierarchical model or just a minor extension to it, it is worthwhile to explore the dynamic behavior characterizing the reversible phenotypic plasticity. In this study we compare the hierarchical model and the reversible mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 47 publications
0
20
0
Order By: Relevance
“…Having made a case for reversible (correctable) phenotype switching enabled by developmental phenotypic plasticity, what might we speculate to be the selection pressures leading to its evolution? Advantages to mature organisms of reversible phenotype switching, as well as its evolution, have received considerable attention -for an entry into the literature see Gabriel (2005), Gabriel (2006), Piersma and van Gils (2010), Berman (2016), Chen et al (2016), Pfab et al (2016), Lazaro et al (2019), and Ratikainen and Kokko (2019). Yet, as Beaman et al (2016) state, ".…”
Section: Reversible Phenotype Switching As a Bridge During Periods Ofmentioning
confidence: 99%
“…Having made a case for reversible (correctable) phenotype switching enabled by developmental phenotypic plasticity, what might we speculate to be the selection pressures leading to its evolution? Advantages to mature organisms of reversible phenotype switching, as well as its evolution, have received considerable attention -for an entry into the literature see Gabriel (2005), Gabriel (2006), Piersma and van Gils (2010), Berman (2016), Chen et al (2016), Pfab et al (2016), Lazaro et al (2019), and Ratikainen and Kokko (2019). Yet, as Beaman et al (2016) state, ".…”
Section: Reversible Phenotype Switching As a Bridge During Periods Ofmentioning
confidence: 99%
“…Some other researches laid emphasis on the role of the phenotypic plasticity in transient dynamics. It was shown that an interesting overshoot phenomenon of CSCs observed in experiment can be well explained by de-differentiation from non-CSCs to CSCs [17,18]. Besides, Leder et al studied mathematical models of pdgf-driven glioblastoma and revealed that the effectiveness of radiotherapy is quite sensitive to the capability of de-differentiation from differentiated sensitive cells to stemlike resistant cells [19]; Jilkine and Gutenkunst studied the effect of de-differentiation on time to mutation acquisition in cancers [20]; Chen et al studied transition model between endocrine therapy responsive and resistant states in breast cancer by Landscape Theory [21]; Dhawan et al showed with mathematical modeling that exposure to hypoxia enhanced the plasticity and heterogeneity of cancer cell populations [22]; Tonekaboi et al investigated how cellular plasticity behaves differently in small and large cancer cell populations [23].…”
Section: Introductionmentioning
confidence: 90%
“…These findings clearly demonstrated that cancer cells are actually extremely plastic and that microenvironmental conditions can influence and drive the bidirectional interconversion between CSCs and non-CSCs phenotypes. Recently several theoretical multi-phenotypic models that include, interconversion and cellular plasticity has been useful in predicting and validating this new paradigm[ 58 - 60 ].…”
Section: The Existence Of Multiple Subpopulations Of Cancer Cellsmentioning
confidence: 99%